Rumus Indeks Ketidaknyamanan Suatu Wilayah - Sugiasih, Mrs. (Jurnal Fourier, 2013)
Index of discomfort can be determined, this value is to accommodate everyone at level howÂ  humans are considered to be comfortable on a place. There are three who wrote formulas i.e., Discomfort Index (DI), temperature Humidity Index (THI) and Comfort Index (CI). In addition to air temperature, air humidity, wind speed there that affect the comfort of a place, such as the density of buildings, distance to the center of the industry, the distance to the center of the trade, the distance to the main street, the coverage of vegetation in the area of the settlements.